Very-High-Energy Outburst of Markarian 501 in May 2009 - Aliu, E. (2016)
The very high energy (VHE; E> 100 GeV) blazar Markarian 501 was observed between April 17 and May 5 (MJD 54 938-54 956), 2009, as part of an extensive multi-wavelength campaign from radio to VHE. Strong VHE γ-ray activity was detected on May 1st with Whipple and VERITAS, when the flux (E > 400 GeV) increased to 10 times the pre-flare baseline flux (3.9 × 10-11 ph cm-2 s-1), reaching five times the flux of the Crab Nebula. This coincided with a decrease in the optical polarization and a rotation of the polarization angle by 15°. This VHE flare showed a fast flux variation with an increase of a factor ∼4 in 25 min, and a falling time of ∼50 min. We present the observations of the quiescent state previous to the flare and of the high state after the flare, focusing on the flux and spectral variability from Whipple, VERITAS, Fermi-LAT, RXTE, and Swift combined with optical and radio data.